PERKEMBANGAN EKONOMI USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2008 DAN FIQIH SIYASAH - Rofii, Rofii; Abdur Rahim (LPSDI Bina Patria, 2024)
The presence of micro, small and medium enterprises plays an important role in encouraging economic growth by stimulating various economic sectors. These MSMEs are the largest contributors to the national economy and represent the community's active participation in economic activities. Over time, MSMEs have proven to be a reliable source of stability during times of crisis, because they create jobs and provide added value to the economy. The aim of this research is to determine the economic development of micro, small and medium enterprises based on law number 20 of 2008 and to determine the economic development of micro, small and medium enterprises based on siyasah fiqh. The research method uses a type of library (Library Research), namely research by examining and analyzing written sources regarding Law number 20 of 2008 concerning MSMEs, the Book of Management & Finance for Micro, Small and Medium Enterprises authored by Putu Krisna Adwitya Sanjaya and I Putu Nuratama is a CV publisher and supplemented from book and journal sources related to the economic development of Micro, Small and Medium Enterprises (MSMEs). The study's findings demonstrate that, in accordance with Law Number 20 of 2008, Micro, Small, and Medium-Sized Enterprises have made good progress toward achieving the goals of a just, balanced, and developing national economy as well as expanding and strengthening their capacity to operate as strong, independent businesses that generate jobs, promote equitable income distribution, spur economic growth, and help lift people out of poverty. On the other hand, the perspective of siyasah jurisprudence on micro, small and medium enterprises is as follows: government policy regarding the growth of these businesses is included in the understanding of the supremacy of law in the siyasah of reciprocal relations between the government and citizens. as well as mandatory citizen rights